A high-efficiency, environmentally friendly, low-VOC hot melt adhesive and its preparation method and application
By adding modified resins and functional fillers to environmentally friendly low VOC hot melt adhesives, a strong intermolecular force and molecular chain network is formed, which solves the problem of performance balance between hot melt adhesives when reducing VOC emissions, and achieves efficient and environmental protection Multi-performance improvement of low-VOC hot melt adhesive.
Patent Information
- Application Number
- CN202411506435.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The existing environmentally friendly low VOC hot melt adhesives are difficult to maintain sufficient adhesion, waterproofness, aging resistance and corrosion resistance while reducing VOC emissions.
By adjusting the formula of hot melt adhesive, adding modified resins and functional fillers, a good intermolecular action force and molecular chain network is formed, which enhances the dispersion and active connection of functional fillers, reduces micropore pore size, and improves waterproofing, aging resistance and stickiness resistance. Connect performance.
It achieves the waterproof, aging resistance, corrosion resistance and bonding properties of hot melt adhesives while maintaining low VOC release characteristics, meets the needs of diverse performances, and obtains excellent application prospects.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of hot melt adhesives, and in particular to a highly efficient, environmentally friendly, low-VOC hot melt adhesive and a preparation method and application thereof. Background Art
[0002] The development background of environmentally friendly low-VOC hot melt adhesives is mainly based on considerations of environmental protection and human health. Traditional solvent-based adhesives contain a high amount of VOC, which not only pollutes the environment, but may also have adverse effects on human health. Therefore, in recent years, more and more environmentally friendly hot melt adhesives have emerged, especially those that can significantly reduce VOC emissions. This type of hot melt adhesive achieves a more environmentally friendly and safer application by adjusting the formula or using new polymerization technology.
[0003] For example, in the automotive industry or the building decoration industry, in order to improve the air quality inside cars and buildings, environmentally friendly interior bonding hot melt adhesives have been developed. This adhesive does not contain VOC components, has no pungent odor, has a fast curing speed, and has a high solid content, making it very suitable for automated production. Similarly, in other industries such as flexible packaging and furniture materials, there is a gradual tendency to use environmentally friendly hot melt adhesives to replace traditional solvent-based adhesives.
[0004] Although environmentally friendly low-VOC hot melt adhesives have many advantages, they still face some technical challenges in practical applications, such as the problem of hot melt adhesive performance balance. While reducing VOC, ensuring that the hot melt adhesive still has sufficient adhesion, persistence, waterproofness, aging resistance, corrosion resistance and high temperature stability is a considerable challenge, because sometimes in order to achieve the goal of low VOC, the basic performance of the hot melt adhesive may be affected.
[0005] Therefore, in order to better solve the above problems, the present application provides a high-efficiency, environmentally friendly, low-VOC release hot melt adhesive and a preparation method. The hot melt adhesive prepared in the present application not only has excellent environmental friendliness and low VOC release, but also can maintain good waterproof, corrosion resistance, aging resistance and adhesion properties. It can meet the diverse performance requirements of low-VOC release hot melt adhesives in existing packaging, automobile manufacturing, furniture, architectural decoration and other industries, thereby obtaining excellent application prospects. Summary of the invention
[0006] In order to solve the above problems, the first aspect of the present application provides a high-efficiency, environmentally friendly, low-VOC hot melt adhesive. The raw materials, calculated by mass, are: 60 to 80 parts of polyamide material, 10 to 20 parts of tackifying resin, 10 to 15 parts of modified resin, 15 to 25 parts of functional filler, 1 to 2 parts of antioxidant, 3 to 8 parts of flow aid, and 1 to 1.5 parts of light stabilizer.
[0007] As a preferred solution, the mass ratio of the polyamide material, the modified resin and the functional filler is (65-75): (12-15): (17-24).
[0008] As a preferred solution, the mass ratio of the polyamide material, the modified resin and the functional filler is (68-72): (13-14): (18-22).
[0009] As a preferred solution, the mass ratio of the polyamide material, the tackifying resin and the flow aid is (65-75): (11-17): (4-7).
[0010] As a preferred solution, the mass ratio of the polyamide material, the tackifying resin and the flow aid is (68-72): (12-15): (5-6).
[0011] As a preferred solution, the polyamide material is fiber-reinforced polyamide resin.
[0012] As a preferred solution, the glass fiber content in the polyamide material is 10-20wt%.
[0013] As a preferred solution, the tackifying resin is at least one of hydrogenated C5 resin, hydrogenated C9 petroleum resin, catechol formaldehyde resin, and styrene block resin.
[0014] As a preferred solution, the tackifying resin is hydrogenated C5 resin.
[0015] As a preferred solution, the preparation method of the modified resin comprises the following steps: S1: adding hydroxyethyl acrylate, dodecyl acrylate and glycidyl acrylate to acryloyl chloride, introducing nitrogen, adding an initiator, heating to 70-80°C for reaction for 3-3.5 hours to generate a front-end polymer; S2: mixing the front-end polymer with acrylamide, adding deionized water and an initiator, reacting at 88-92°C for 5-5.5 hours under nitrogen atmosphere protection to obtain a solution of a polymer product; S3: adding triethanolamine to the solution of the polymer product, stirring at 50-60°C for 1-1.5 hours, then filtering the polymer product, washing it with acetone for 2-3 times, and obtaining the product after complete ventilation and drying.
[0016] As a preferred solution, the mass ratio of hydroxyethyl acrylate, dodecyl acrylate and glycidyl acrylate is (8-10): (0.5-1): (1.5-3).
[0017] As a preferred solution, the initiator is potassium persulfate or ammonium persulfate.
[0018] As a preferred solution, the mass ratio of the front-end polymer, acrylamide and triethanolamine is (6-8): (25-30): (2-4).
[0019] In this application, by adding the above-mentioned modified resin, the waterproof, aging corrosion resistance and bonding performance of the hot melt adhesive can be effectively improved under the premise of maintaining good environmental protection and low VOC characteristics. The modified resin added to the system can form a good intermolecular force with the functional filler added in this application, so as to realize the carrier fixation of the modified resin for the functional filler, and then when the molecular chain network in the hot melt adhesive system is constructed, the dispersibility of the functional filler in it is greatly enhanced, and the active connection of the organic molecular chain to the functional filler is realized, and the pore size of the micropores of the functional filler in the hot melt adhesive system is reduced, and the negative effects of the large pores of the filler on the resistance to water penetration, the resistance to the free active group and the cohesion of the system are avoided, so as to obtain good waterproof and aging corrosion resistance, and weaken the negative effect on adhesion; in addition, the addition of the modified resin can also effectively enhance the mutual entanglement of the organic molecular chain network in the system, thereby greatly enhancing the molecular compactness inside the system, enhancing the steric hindrance of the functional filler, reducing the probability of internal reaction, and improving the water penetration resistance, so as to obtain excellent waterproof, aging and bonding performance.
[0020] As a preferred scheme, the preparation method of the functional filler includes the following steps: S1: adding aluminum chloride, zinc nitrate and zinc oxide to DMF solution and ultrasonically dispersing them evenly, adding sodium dodecylbenzenesulfonate, glutaric anhydride and 3-aminopropyltriethoxysilane, heating to 65-75°C and keeping warm for 2-3 hours, centrifuging the product, washing and vacuum drying to obtain mixed particles; S2: adding the mixed particles to a mixed solution of methanol and DMF, and simultaneously adding dropwise a DMF solution containing p-aminobenzoic acid and a methanol solution containing dimethylimidazole, the dropping time is 1-1.5 hours, the dropping reaction temperature is 60-80°C, after the dropping is completed, the reactor is sealed, and the temperature is raised to 120-130°C, and the reaction is stirred at 120-150rpm for 12-15 hours. After the reaction is completed, it is naturally cooled to room temperature, centrifuged, washed with methanol for 2-3 times, and vacuum dried to obtain the product.
[0021] As a preferred embodiment, the mass ratio of aluminum chloride, zinc nitrate, zinc oxide, sodium dodecylbenzene sulfonate, glutaric anhydride and 3-aminopropyltriethoxysilane is (4-4.8): (1-1.5): (0.8-1.2): (0.3-0.5): (1.5-2): (0.2-0.3).
[0022] As a preferred embodiment, the mass ratio of aluminum chloride, zinc nitrate, zinc oxide, sodium dodecylbenzene sulfonate, glutaric anhydride and 3-aminopropyltriethoxysilane is (4.2-4.5): (1.1-1.3): (0.8-1): (0.3-0.4): (1.8-2): (0.2-0.25).
[0023] As a preferred solution, the average particle size of the zinc oxide is 15-25 nm.
[0024] As a preferred solution, the mass ratio of methanol to DMF in the mixed solution of methanol and DMF is (2-2.5):1.
[0025] As a preferred solution, in the mixed particles, the mass ratio of p-aminobenzoic acid and dimethylimidazole is (3-3.5): (1.4-1.8): (0.8-1.1).
[0026] As a preferred solution, the average particle size of the functional filler is 550-650 nm.
[0027] The addition of the above-mentioned functional filler in the present application can effectively improve the waterproof, corrosion-resistant and aging-resistant properties of the hot melt adhesive, and reduce its negative effect on adhesion. The functional filler prepared in the present application can form a good interaction force with the resin system through the surface-coated active zinc oxide, greatly enhance the stability and dispersion fixation of the functional filler in the system, thereby reducing its pore size in the system, avoiding its dispersion effect on cohesion, and can also play a good connection and support role through the interaction force with the system molecular chain; on the other hand, the composite structure formed by the functional filler can guide the water molecules in advance through the zinc oxide on the surface, and then form a fixed adsorption of the water molecules through the internal framework composite structure when the water molecules continue to penetrate, and because the composite structure is formed to strengthen the fixing strength of the water molecules, it can play an excellent role in removing internal water molecules in long-term use and high temperature environment, and can remain non-desorbed in the general use environment temperature, thereby avoiding the rapid penetration of water molecules and corrosive groups with water molecules as the main carrier, effectively improving the waterproof, aging corrosion and mechanical properties of the hot melt adhesive.
[0028] As a preferred solution, the antioxidant is at least one of antioxidant 1010, antioxidant 164, antioxidant 168, antioxidant 1076 and antioxidant CA.
[0029] As a preferred solution, the antioxidant is antioxidant 1076.
[0030] As a preferred solution, the flow aid is at least one of polyethylene wax, polypropylene wax, microcrystalline wax, paraffin wax and Fischer-Tropsch wax.
[0031] As a preferred solution, the flow aid is a combination of polyethylene wax and paraffin wax.
[0032] As a preferred solution, the mass ratio of the polyethylene wax to the paraffin wax is (3-3.5): (0.4-0.8).
[0033] As a preferred solution, the light stabilizer is a benzotriazole light stabilizer.
[0034] As a preferred solution, the light stabilizer is at least one of Tinuvin 770, Tinuvin 360 and Tinuvin 384.
[0035] As a preferred solution, the light stabilizer is Tinuvin 770.
[0036] The second aspect of the present application provides a method for preparing the above-mentioned high-efficiency, environmentally friendly, low-VOC hot melt adhesive, which specifically includes the following steps: S1: Add polyamide material into a container and heat it to 165~175°C, add tackifying resin, modified resin, antioxidant, flow aid, light stabilizer and functional filler in sequence under stirring at 80~100rpm, stir for 30~40min each time, and finally heat to 190~200°C after adding the functional filler, and continue stirring for 40~50min to obtain a uniform mixture; S2: Keep the mixture warm and deaerate at a vacuum degree of 0.09~0.11MPa for 15~25min, cool to 120~140°C after deaeration, add hot melt adhesive mold to form, then naturally cool to 20~35°C, discharge and seal to obtain.
[0037] The third aspect of the present application provides an application of the above-mentioned high-efficiency, environmentally friendly, low-VOC release hot melt adhesive in packaging, automobile manufacturing, furniture, and architectural decoration.
[0038] The beneficial effects of this application are:
[0039] 1. The present application provides a high-efficiency, environmentally friendly, low-VOC hot melt adhesive, which not only has excellent environmental friendliness and low VOC release, but also has good waterproof, corrosion-resistant, aging-resistant and adhesive properties. It can meet the diverse performance requirements of low-VOC hot melt adhesives in existing packaging, automobile manufacturing, furniture, architectural decoration and other industries, thereby achieving excellent application prospects.
[0040] 2. The present application provides a high-efficiency, environmentally friendly, low-VOC hot melt adhesive, in which the addition of modified resin can form good intermolecular forces with the functional filler added in the present application, thereby realizing the carrier fixation of the modified resin for the functional filler, and then when the molecular chain network in the hot melt adhesive system is constructed, the dispersibility of the functional filler therein is greatly enhanced, and the active connection of the organic molecular chain to the functional filler is realized, the pore size of the micropores of the functional filler in the hot melt adhesive system is reduced, and the negative effects of the large pores existing in the previous fillers on the resistance to water penetration, the resistance to the free active groups and the cohesion of the system are avoided, thereby obtaining good waterproof and aging corrosion resistance, and reducing the negative effects on adhesion; in addition, the addition of modified resin can also effectively enhance the mutual entanglement of the organic molecular chain network in the system during construction, thereby greatly enhancing the molecular compactness inside the system, enhancing the steric hindrance of the functional filler, reducing the probability of internal reactions, and improving the resistance to water penetration.
[0041] 3. In the present application, a high-efficiency, environmentally friendly, low-VOC hot melt adhesive is provided. The added functional filler can form a good interaction force with the resin system through the active zinc oxide coated on the surface, greatly enhancing the stability and dispersion fixation of the functional filler in the system, thereby reducing its pore size in the system, avoiding its dispersion effect on the cohesive force, and can also play a good connection and support role through the interaction force with the system molecular chain; on the other hand, the composite structure formed by the functional filler can guide the water molecules in advance through the zinc oxide on the surface, and then form fixed adsorption of the water molecules through the internal framework composite structure when the water molecules continue to penetrate, and because the composite structure forms a stronger fixation strength for the water molecules, it can play an excellent role in removing internal water molecules under long-term use and high temperature environment, and can remain non-desorbed at the general use environment temperature, thereby avoiding the rapid penetration of water molecules and corrosive groups with water molecules as the main carrier, and effectively improving the waterproof, aging corrosion and mechanical properties of the hot melt adhesive. DETAILED DESCRIPTION
[0042] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0043] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0044] Example 1
[0045] Example 1 The first aspect provides a high-efficiency, environmentally friendly, low-VOC hot melt adhesive, the raw materials of which are, by mass: 68.5 parts of polyamide material, 14.5 parts of tackifying resin, 13.6 parts of modified resin, 20.5 parts of functional filler, 1.4 parts of antioxidant, 5.2 parts of flow aid, and 1.2 parts of light stabilizer.
[0046] The polyamide material is a fiber-reinforced polyamide resin with a glass fiber content of 20wt%, which is purchased from the PA9T series product with corresponding content sold by Kuraray.
[0047] The tackifying resin is hydrogenated C5 resin, which is an industrial grade product purchased from Shandong Jinghao Chemical Co., Ltd.
[0048] The preparation method of the modified resin comprises the following steps, calculated by mass: S1: adding 9.5 parts of hydroxyethyl acrylate, 0.8 parts of dodecyl acrylate and 2.2 parts of glycidyl acrylate to 120 parts of acryloyl chloride, introducing nitrogen, adding 0.1 parts of potassium persulfate, heating to 75°C for reaction for 3 hours to generate a front-end polymer; S2: mixing 7.2 parts of the front-end polymer with 28.5 parts of acrylamide, adding 300 parts of deionized water and 0.18 parts of potassium persulfate, reacting at 90°C for 5 hours under nitrogen atmosphere protection to obtain a solution of a polymer product; S3: adding 2.5 parts of triethanolamine to the solution of the polymer product, stirring at 55°C for 1 hour, filtering the polymer product, washing it with acetone for 3 times, and obtaining it after complete ventilation and drying.
[0049] The preparation method of the functional filler comprises the following steps, calculated by mass: S1: adding 4.4 parts of aluminum chloride, 1.2 parts of zinc nitrate and 0.9 parts of zinc oxide to 120 parts of DMF solution and uniformly dispersing by ultrasonic, adding 0.32 parts of sodium dodecylbenzenesulfonate, 1.9 parts of glutaric anhydride and 0.22 parts of 3-aminopropyltriethoxysilane, heating to 70°C and keeping warm for 2.5 hours, centrifuging and filtering the product, washing and vacuum drying to obtain mixed particles; S2: adding 3.3 parts of mixed particles Add to a mixed solution of 100 parts of methanol and DMF, and at the same time, add dropwise a DMF solution containing 1.6 parts of p-aminobenzoic acid (30 parts in total) and a methanol solution containing 1 part of dimethylimidazole (30 parts in total). The dropping time is 1 hour, and the dropwise reaction temperature is 70°C. After the dropwise addition is completed, seal the reactor, heat to 125°C, stir at 120rpm for 14 hours, and naturally cool to room temperature after the reaction is completed. Centrifuge and filter, wash with methanol for 3 times, and obtain the product after vacuum drying.
[0050] The average particle size of zinc oxide is 18 nm; the average particle size of the functional filler is 594 nm.
[0051] The mass ratio of methanol to DMF in the mixed solution of methanol and DMF is 2:1.
[0052] The antioxidant is antioxidant 1076; the flow aid is a combination of polyethylene wax and paraffin wax, with a mass ratio of 3.4:0.6; the polyethylene wax is purchased from the industrial-grade polyethylene wax product sold by Wuhan Xindongyi Chemical Co., Ltd.; the paraffin wax is purchased from the industrial-grade paraffin product sold by Wuhan Xindongyi Chemical Co., Ltd.
[0053] The light stabilizer is Tinuvin 770.
[0054] The second aspect of the present embodiment provides a method for preparing the above-mentioned high-efficiency, environmentally friendly, low-VOC hot melt adhesive, which specifically includes the following steps: S1: Add polyamide material into a container and heat to 165°C, add tackifying resin, modified resin, antioxidant, flow aid, light stabilizer and functional filler in sequence under stirring at 100rpm, stir for 35 minutes each time, and after the functional filler is added, heat to 200°C and continue stirring for 45 minutes to obtain a uniform mixture; S2: The mixture is continuously kept warm and degassed at a vacuum degree of 0.09MPa for 20 minutes. After degashing, cool to 130°C, add hot melt adhesive mold to form, then naturally cool to 30°C, discharge and seal to obtain.
[0055] Example 2
[0056] The specific implementation of this embodiment is basically the same as that of Example 1, except that: 75 parts of polyamide material, 11.5 parts of tackifying resin, 12.2 parts of modified resin, 23.5 parts of functional filler, 1.6 parts of antioxidant, 4.2 parts of flow aid, and 1.3 parts of light stabilizer.
[0057] Example 3
[0058] The specific implementation of this embodiment is basically the same as that of Example 1, except that: 65.8 parts of polyamide material, 16.2 parts of tackifying resin, 15 parts of modified resin, 17.8 parts of functional filler, 1.2 parts of antioxidant, 6.5 parts of flow aid, and 1.4 parts of light stabilizer.
[0059] Comparative Example 1
[0060] The specific implementation of this comparative example is basically the same as that of Example 1, except that: 80.8 parts of polyamide material, 20.5 parts of tackifying resin, 5.6 parts of modified resin, 24.5 parts of functional filler, 1.4 parts of antioxidant, 5.2 parts of flow aid, and 1.2 parts of light stabilizer.
[0061] Comparative Example 2
[0062] The specific implementation of this comparative example is basically the same as that of Example 1, except that: 78.5 parts of polyamide material, 14.5 parts of tackifying resin, 15.6 parts of modified resin, 8.5 parts of functional filler, 1.4 parts of antioxidant, 5.2 parts of flow aid, and 1.2 parts of light stabilizer.
[0063] Comparative Example 3
[0064] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified resin comprises the following steps, calculated by mass: S1: adding 15.5 parts of hydroxyethyl acrylate, 0.2 parts of dodecyl acrylate and 0.5 parts of glycidyl acrylate to 120 parts of acryloyl chloride, introducing nitrogen, adding 0.1 parts of potassium persulfate, heating to 75°C and reacting for 3 hours to generate a front-end polymer; S2: mixing 7.2 parts of the front-end polymer with 28.5 parts of acrylamide, adding 300 parts of deionized water and 0.18 parts of potassium persulfate, reacting at 90°C for 5 hours under nitrogen atmosphere protection, and obtaining a solution of a polymer product; S3: adding 2.5 parts of triethanolamine to the solution of the polymer product, stirring at 55°C for 1 hour, then filtering the polymer product, washing it with acetone for 3 times, and obtaining it after complete ventilation and drying.
[0065] Comparative Example 4
[0066] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the modified resin comprises the following steps, calculated by mass: S1: adding 9.5 parts of hydroxyethyl acrylate, 0.8 parts of dodecyl acrylate and 2.2 parts of glycidyl acrylate to 120 parts of acryloyl chloride, introducing nitrogen, adding 0.1 parts of potassium persulfate, heating to 75°C and reacting for 3 hours to generate a front-end polymer; S2: mixing 4.2 parts of the front-end polymer with 34.5 parts of acrylamide, adding 300 parts of deionized water and 0.18 parts of potassium persulfate, reacting at 90°C for 5 hours under nitrogen atmosphere protection, and obtaining a solution of a polymer product; S3: adding 1.2 parts of triethanolamine to the solution of the polymer product, stirring at 55°C for 1 hour, then filtering the polymer product, washing it with acetone for 3 times, and obtaining it after complete ventilation and drying.
[0067] Comparative Example 5
[0068] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the functional filler comprises the following steps, by mass: S1: adding 6.8 parts of aluminum chloride, 0.6 parts of zinc nitrate and 0.4 parts of zinc oxide to 120 parts of DMF solution and uniformly dispersing by ultrasonication, adding 0.32 parts of sodium dodecylbenzene sulfonate, 1 part of glutaric anhydride and 0.12 parts of 3-aminopropyltriethoxysilane, heating to 70°C and keeping warm for 2.5 hours, centrifuging the product, washing and vacuum drying to obtain mixed particles S2: Add 3.3 parts of the mixed particles to a mixed solution of 100 parts of methanol and DMF, and simultaneously add dropwise a DMF solution containing 1.6 parts of p-aminobenzoic acid (30 parts in total) and a methanol solution containing 1 part of dimethylimidazole (30 parts in total). The dropping time is 1 hour, and the dropping reaction temperature is 70°C. After the dropping is completed, the reactor is sealed, and the temperature is raised to 125°C. The reaction is stirred at 120rpm for 14 hours. After the reaction is completed, it is naturally cooled to room temperature, centrifuged, washed with methanol for 3 times, and vacuum dried to obtain the product.
[0069] The average particle size of the functional filler is 507 nm.
[0070] Comparative Example 6
[0071] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the functional filler comprises the following steps, by mass: S1: adding 6.4 parts of aluminum chloride, 1.2 parts of zinc nitrate and 0.9 parts of zinc oxide to 120 parts of DMF solution and uniformly dispersing by ultrasonication, adding 0.32 parts of sodium dodecylbenzene sulfonate, 1.9 parts of glutaric anhydride and 0.22 parts of 3-aminopropyltriethoxysilane, heating to 70°C and keeping warm for 2.5 hours, centrifuging the product, washing and vacuum drying to obtain mixed particles S2: Add 1.5 parts of the mixed particles to a mixed solution of 100 parts of methanol and DMF, and simultaneously add dropwise a DMF solution containing 2.2 parts of p-aminobenzoic acid (30 parts in total) and a methanol solution containing 1.8 parts of dimethylimidazole (30 parts in total). The dropping time is 1 hour, and the dropping reaction temperature is 70°C. After the dropping is completed, the reactor is sealed, and the temperature is raised to 125°C. The reaction is stirred at 120rpm for 14 hours. After the reaction is completed, it is naturally cooled to room temperature, centrifuged, washed with methanol for 3 times, and vacuum dried to obtain the product.
[0072] The average particle size of the functional filler is 687 nm.
[0073] Comparative Example 7
[0074] The specific implementation of this comparative example is basically the same as that of Example 1, except that the average particle size of zinc oxide is 38 nm; and the average particle size of the functional filler is 702 nm.
[0075] Performance Evaluation
[0076] Peel strength test: The test substrate is a polyethylene plate. The peel strength is tested at an angle of 180° and a constant tensile rate of 100 mm / min. The test value is the average value of 10 tests and is recorded in Table 1.
[0077] Tensile strength test: The hot melt adhesives prepared in the examples and comparative examples were tested for tensile strength with reference to GB / T 528-2009. The test values were averaged from 10 tests and recorded in Table 1.
[0078] VOC content: the hot melt adhesives prepared in the embodiments and comparative examples were tested for VOC content according to the reference standard GB 33372-2020. The maximum allowable value of the standard is 50 g / kg, the minimum detection limit is 1 g / kg, and the qualified line of the test in this application is ≤7.5 g / kg. 50 groups of samples were tested in each group, and the qualified rate was recorded in Table 1.
[0079] Waterproof test: After curing the hot melt adhesives prepared in the embodiments and comparative examples, samples of 2 cm×2 cm×0.2 cm were prepared. The surface water contact angle was tested by the sessile drop method. The test water drop was 2.5 μL and the test time was 30 s. The test value was the average of 10 tests and recorded in Table 1.
[0080] Aging resistance test: After curing the hot melt adhesives prepared in the embodiments and comparative examples, samples of 2 cm × 2 cm × 0.2 cm were prepared and placed in a constant temperature and humidity chamber at 68 ± 2 ° C and 75 ± 3% relative humidity for 6 months. After 6 months, record whether the samples have yellowing, oxidation, cracking, blistering and hydrolysis damage. If so, it is recorded as unqualified, otherwise it is qualified. 50 samples were tested in each group to record the qualified rate of the samples, which is recorded in Table 1.
[0081] Table 1 Performance test results
[0082]
[0083] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 and 2 of the present application have obvious advantages over comparative examples 1 to 7 in terms of mechanical properties, waterproof properties, bonding properties and aging resistance. This is mainly due to the combined effect of the modified resin, functional particles and other matching schemes specified in the present application. Comparative examples 1 to 7 did not adopt the technical scheme specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests, which further proves the necessity of the technical scheme specified in the present application for the technical effect of the present application and solving technical problems.
Claims
1. A highly efficient and environmentally friendly hot melt adhesive with low VOC release, characterized by: In parts by mass, the raw materials are: 60-80 parts of polyamide material, 10-20 parts of tackifying resin, 10-15 parts of modified resin, 15-25 parts of functional filler, 1-2 parts of antioxidant, 3-8 parts of flow aid, 1-1.5 parts of light stabilizer; The polyamide material is a fiber-reinforced polyamide resin; The glass fiber content in the polyamide material is 10-20wt%; The tackifying resin is at least one of hydrogenated C5 resin, hydrogenated C9 petroleum resin, catechol formaldehyde resin, and styrene block resin; The preparation method of the modified resin comprises the following steps: S1: adding hydroxyethyl acrylate, dodecyl acrylate and glycidyl acrylate to acryloyl chloride, introducing nitrogen, adding an initiator, heating to 70-80° C. for reaction for 3-3.5 hours to generate a front-end polymer; S2: mixing the front-end polymer with acrylamide, adding deionized water and an initiator, reacting at 88-92° C. for 5-5.5 hours under nitrogen atmosphere protection to obtain a solution of a polymer product; S3: adding triethanolamine to the solution of the polymer product, stirring at 50-60° C. for 1-1.5 hours, filtering the polymer product, washing it with acetone for 2-3 times, and obtaining the product after complete ventilation and drying; The mass ratio of hydroxyethyl acrylate, dodecyl acrylate and glycidyl acrylate is (8-10): (0.5-1): (1.5-3); The mass ratio of the front-end polymer, acrylamide and triethanolamine is (6-8): (25-30): (2-4); The preparation method of the functional filler comprises the following steps: S1: adding aluminum chloride, zinc nitrate and zinc oxide to a DMF solution and uniformly dispersing them by ultrasonication, adding sodium dodecylbenzenesulfonate, glutaric anhydride and 3-aminopropyltriethoxysilane, heating to 65-75°C and keeping the temperature for 2-3 hours, centrifugally filtering the product, washing and vacuum drying to obtain mixed particles; S2: adding the mixed particles to a mixed solution of methanol and DMF, and simultaneously dripping a DMF solution containing p-aminobenzoic acid and a methanol solution containing dimethylimidazole, the dripping time is 1-1.5 hours, the dripping reaction temperature is 60-80°C, sealing the reactor after the dripping is completed, heating to 120-130°C, stirring at 120-150rpm for 12-15 hours, cooling naturally to room temperature after the reaction is completed, centrifugally filtering, washing with methanol for 2-3 times, and vacuum drying to obtain the product; The mass ratio of the aluminum chloride, zinc nitrate, zinc oxide, sodium dodecylbenzene sulfonate, glutaric anhydride and 3-aminopropyltriethoxysilane is (4-4.8): (1-1.5): (0.8-1.2): (0.3-0.5): (1.5-2): (0.2-0.3); The mass ratio of p-aminobenzoic acid and dimethylimidazole in the mixed particles is (3-3.5): (1.4-1.8): (0.8-1.1); The average particle size of the zinc oxide is 15-25 nm; The average particle size of the functional filler is 550-650 nm.
2. The high-efficiency, environmentally friendly, low-VOC hot melt adhesive according to claim 1, characterized in that: The mass ratio of the polyamide material, the modified resin and the functional filler is (65-75): (12-15): (17-24).
3. The high-efficiency, environmentally friendly, low-VOC hot melt adhesive according to claim 2, characterized in that: The mass ratio of the polyamide material, the tackifying resin and the flow aid is (65-75): (11-17): (4-7).
4. The high-efficiency, environmentally friendly, low-VOC hot melt adhesive according to claim 3, characterized in that: The antioxidant is at least one of antioxidant 1010, antioxidant 164, antioxidant 168, antioxidant 1076 and antioxidant CA.
5. The high-efficiency, environmentally friendly, low-VOC hot melt adhesive according to claim 4, characterized in that: The flow aid is at least one of polyethylene wax, polypropylene wax, microcrystalline wax, paraffin wax and Fischer-Tropsch wax.
6. The high-efficiency, environmentally friendly, low-VOC hot melt adhesive according to claim 5, characterized in that: The flow aid is a composition of polyethylene wax and paraffin wax; the mass ratio of the polyethylene wax to the paraffin wax is (3-3.5): (0.4-0.8).
7. The method for preparing a high-efficiency, environmentally friendly, low-VOC hot melt adhesive according to any one of claims 1 to 6, characterized in that: The specific steps include: S1: Add polyamide material into a container and heat it to 165~175℃, then add tackifying resin, modified resin, antioxidant, flow aid, light stabilizer and functional filler in sequence while stirring at 80~100rpm. Stir for 30~40min each time. Finally, after adding the functional filler, heat the mixture to 190~200℃ and continue stirring for 40~50min to obtain a uniform mixture. S2: Keep the mixture warm and degas at a vacuum degree of 0.09~0.11MPa for 15~25min. After degassing, cool it to 120~140℃, add hot melt adhesive to form the mold, then naturally cool to 20~35℃, discharge and seal.
8. Use of the high-efficiency, environmentally friendly, low-VOC hot melt adhesive according to any one of claims 1 to 6 in packaging, automobile manufacturing, furniture, and architectural decoration.
Citation Information
Patent Citations
Method for improving melt strength of polyester resin
CN103626982A
Antibacterial hot melt adhesive and preparation method thereof
CN107118714A